2019
DOI: 10.1002/adma.201808024
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse and Uniform Mesoporous Silicate Nanosensitizers Achieve Low‐Dose X‐Ray‐Induced Deep‐Penetrating Photodynamic Therapy

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/adma.201808024. Photodynamic TherapyAs a powerful therapeutic methodology used for over a century, radiotherapy (RT) has garnered much attention in clinical use. [1] However, the efficacy of RT has been limited due to its toxic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 27 publications
0
109
0
Order By: Relevance
“…A recent publication suggests that suitable metal dopants (Zn, Mn) in silicate act as nanoscintillators (ZSM) and produce visible X-ray luminescence (450-900 nm); [298] this luminescence then stimulates a conjugated PS, Rose Bengal (RB). This ZSM-RB conjugate was conjugated to RGD peptide forming RB-ZSM-RGD that ensures high specific binding to the U87MG cells.…”
Section: Scintillating Inorganic Nanoparticles Combined With Photosenmentioning
confidence: 99%
“…A recent publication suggests that suitable metal dopants (Zn, Mn) in silicate act as nanoscintillators (ZSM) and produce visible X-ray luminescence (450-900 nm); [298] this luminescence then stimulates a conjugated PS, Rose Bengal (RB). This ZSM-RB conjugate was conjugated to RGD peptide forming RB-ZSM-RGD that ensures high specific binding to the U87MG cells.…”
Section: Scintillating Inorganic Nanoparticles Combined With Photosenmentioning
confidence: 99%
“…Recent proofof-concept studies using nanoscintillator-photosensitizer conjugates demonstrated that this combinatory approach has a strong therapeutic potential in vitro and in vivo. [13][14][15][16][17][18][19][20][21][22][23][24] Biomedical applications of nanoscintillators are currently mostly centered on this concept of radioluminescence-induced PDT. However, factors by which nanoscintillators can augment radiotherapy outcomes also include a potential synergism with radiotherapy [25] and the use of nanoscintillators that emit UV-C photons to expand the amount and types of DNA damage induced during radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The mesoporous zinc gallogermanates, that is, Zn 3 Ga 2 GeO 8 :Cr 3+ , Yb 3+ , Er 3+ (mZGGOs), were synthesized using a silica templating method as previously described by us. [ 17 ] The as‐prepared mZGGOs displayed typical spherical structures that were monodisperse with uniform size (100.3 ± 10.6 nm) ( Figure a). Clear pore structures were observed in the high‐resolution transmission electron microscopy (HR‐TEM) image (Figure 1b), and nitrogen adsorption isotherm confirmed the formation of pores with a high surface area (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%